Sistem Pendukung Keputusan Penentuan Penerima Beasiswa Cendikia Baznas(BCB)Kota Dumai Menggunakan Metode Combined Compromise Solution (CoCoSo) - Sarah Zulvianty; Tri Handayani; Ari Sellyana (Sekolah Tinggi Teknologi Dumai, 2024)
The National Zakat Amil Agency (BAZNAS) is an official body formed by the government based on the Decree of the President of the Republic of Indonesia which has the task and function of collecting and distributing zakat, infaq and alms at the national level. The Cendikia Baznas Scholarship (BCB) Dumai City is one of the Dumai Smart programs which is intended for prospective and underprivileged students from Dumai City who will study at the Tazkia Bogor Islamic Institute (IAI) with all costs borne by Baznas Dumai City. Dumai City Baznas always provides BCB scholarships with a quota of five people who will be selected to undertake 4 years of education at IAI Tazkia Bogor. The selection of BCB scholarship recipients is based on several criteria such as grade transcripts, parents' income, registration form, parental approval letter, achievements, school recommendation letters, certificates of incapacity, participation in organizations, academic tests, and writing the essay